Faktor-Faktor Yang Mempengaruhi Keberhasilan Implementasi Sistem Informasi Manajemen Barang Milik Negara Di Universitas Negeri Medan - Elmon Tampubolon (Jurnal Manajemen Dan Akuntansi Medan, 2021)
The aim research are analyze and provide empirical evidence of influenced by several factors likes leadership commitment, quantity and quality of human resources and supporting facilities with simultaneous inference and partial for the successful implementation of SIMAK-BMN at the State University of Medan. this research is quantitative research emphasis on testing the causal relationships influence the leadership's commitment, Quantity and Quality of human resources and supporting facilities for the successful implementation of SIMAK -BMN. The research population is all administration staff in state University of Medan which duties in general and equipment field. This research using 38 sample. Data research obtained with give questioner to respondent. Analysis technique used is multiple regression analysis with simultaneous inference and partial. For hypothesis test used F and t test. The analysis result proved that commitment of leadership, the quality of human resources, the quantity of human resources, and good supporting facilities influenced the successful implementation of SIMAK-BMN at the State University of Medan. the analysis partial showed the commitment of leadership, quality of human resources, and supporting facilities have positive influence on successful implementation SIMAK-BMN at University of Medan. However the quantity of human resources didn’t influent on successful implementation SIMAK-BMN